PENGEMBANGAN MEDIA SMART BOX PADA MATA PELAJARAN MATEMATIKA MATERI HUBUNGAN ANTARSATUAN BAKU PANJANG KELAS III SEKOLAH DASAR - Iselia Ayu Wulandari; Yantoro; Ditia Erika Febriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the limited use of mathematics learning media in third-grade elementary schools, which is still dominated by textbooks and whiteboards. Consequently, it has not fully facilitated active student participation or supported the needs of the concrete operational stage of cognitive development. Therefore, this study aims to develop and examine the validity and practicality of Smart Box learning media on the topic of relationships between standard units of length for third-grade elementary school students. This research is a Research and Development (R&D) study using the ADDIE model, which consists of the stages of analysis, design, development, etation, and evaluation. The results of the study show that the Smart Box media was considered valid based on the media expert assessment with a percentage of 77.5%, highly valid according to material experts with 96.67%, and highly valid according to language experts with 100%. In addition, the practicality test results based on teacher responses reached 100%, while student responses reached 96.04%, both categorized as highly practical. Thus, the Smart Box learning media meets the criteria of validity and practicality, making it feasible to be used as mathematics learning media in elementary schools